Motivation of Cadre in Effectiveness in Stimulating The Growth and Development of Children Under Two Years Old in Jambi - Rumita Ena Sari; Ismi Nurwaqiah Ibnu; Adila Solida; Roza Rizana (PT. Anagata Sembagi Education, 2025)
Early childhood development refers to the cognitive, physical, language, motor, social and emotional development of children from conception to 8 years of age. This study aims to analyse the effectiveness of cadres in the stimulation of growth and development of under-two children in Jambi city. This study is a quantitative study with a cross-sectional design. The sample was taken with a multistage technique, namely 118 cadres. Data collection using questionnaires. Data analysis with multiple logistic regression. Based on the results of multivariate analysis, the possibility of growth motivation (PR 10,981 and P value 0,000) was the most influential variable on the effectiveness of cadres in stimulating the growth and development of infants under 2 years. The possibility of growth motivation was the most influential variable on the effectiveness of cadres in stimulating the growth and development of infants under 2 years. It is expected that cadres receive tiered training, cadres become mentors to new cadres, informal education opportunities, and recognition as exemplary cadres.